Analisis Algoritma Sequential Search Pada Aplikasi Pencarian Berita - Furqan, Mhd; Armansyah, A; Kurniawan, Riski Askia (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The algorithm is an approach to be able to compile and manage data efficiently. The Sequential Search algorithm is used to build a mobile-based news search application. The search function is used to validate the data itself. The Sequential Search algorithm has 2 possibilities, namely the best possibility (best case) and the worst case (worst case). In determining a possibility, it takes the complexity of the time algorithm. This study will analyze the Sequential Search algorithm in determining the 2 possibilities that occur in mobile applications. Data is one of the things needed in the development of an application. There are 100 data used by researchers as keywords and researchers will take 5 keywords, namely Earthquake, PDI, Indonesian Education, Floods, and Online Sales to determine the best case and worst case from the Sequential Search algorithm. In determining the speed of time required running time program in units of milliseconds (ms). So that the average time for the earthquake keyword is 0.014189 ms, the PDI keyword is 0.073763 ms, the Indonesian Education keyword is 0.169640 ms, the Flood keyword is 0.206307 ms, and the Online Selling keyword is 0.284086 ms. By obtaining the time from the test, the results of the complexity are also obtained, namely Tmin(n) = 0.014189 ms so that the best case is found in the Earthquake keyword and Tmax(n) = 0.284086 ms so that the worst case is found in the Online Selling keyword. And Tavg(n) = 0.1491375 ms. News API is HTTP REST API which is used to access news after keywords are found